Impact of quality improvement measures on the delivery of allergy immunotherapy: a 2‐year follow‐up. Issue 6 (6th April 2015) - Mattos, Jose L.; Ferguson, Berrylin J.; Lee, Stella
<x xml:space="preserve">Abstract</x> Background Anaphylaxis is the most serious potential complication from allergy treatment with subcutaneous immunotherapy (SCIT). Quality measures were developed with the goal to decrease the incidence of complications resulting from SCIT and improve the safety of care provided. Methods The incidence and characteristics of anaphylaxis episodes resulting from SCIT was measured between 2008 and 2012 prior to implementation of quality measures including vial verification, vial testing, and standardized training across 6 allergy delivery sites. Errors and anaphylaxis rates were then tracked prospectively over a 2‐year period after implementation of these process measures. Results From 2008 to 2012 there were 9 episodes of anaphylaxis or 0.02% of injections/year. Eight patients had sufficient information from which to derive meaningful data. Patient identification error led to anaphylaxis in 2 patients, dosing error in 2, and compounding error in 1 patient. In 2 patients, anaphylaxis occurred with advancement during pollen season, and in 1 patient no clear reason could be identified although she had asthma as a risk factor. After implementation of quality improvement measures the anaphylaxis rate fell to 0 of 8948 injections for years 2013 and 2014. Conclusion Errors in the mixing and administration of allergy serum comprised the majority of identifiable factors that led to anaphylaxis. Implementation of quality measures, including vial verification and vial testing, can improve safety and decrease anaphylaxis rates in the delivery of allergy immunotherapy.